Analysis of confirmatory factors of principals' leadership training of vocational high school - Lia Yuliana; Lantip Diat Prasojo; Awanis Akalili (Jurnal Cakrawala Pendidikan, 2022)
One of the main problems in the course of management in Vocational High School is the principal's leadership training problem. Great leadership training has an impact on improving the quality of schools, the quality of teachers, and the professionalism of teachers in carrying out educational activities. This research aimed to find out what is the result of Confirmatory Factor Analysis (CFA) on leadership training indicators for the principals of Vocational High School based on the perception of teachers, principals, and students. The method used in this research is a quantitative method to find out the result of Confirmatory Factor Analysis leadership training for principals of Vocational High School. This research used a simple random sampling technique with 255 teachers, 57 principals, and 315 students as the sample. The data analysis applied is KMO (Keiser-Meyer-Olkin Measure of Sampling Adequacy) and Bartlett’s Test of Sphericity. Extraction Method with Principal Component Analysis. The result of the study shows that the teacher sample obtained the KMO value 0,737 which indicates sample suitability is high (0,5), and the lowest value of MSA (Measure of Sampling Adequacy) is 0,550. Meanwhile, the highest is 0,852, communalities value and appropriate matrix components, loading factor on all variables have met the requirements above 0,40, and all factors on the leadership training instruments for the principal of Vocational High School have an AVE value greater than 0,5; thus, they have met reliability and can be accepted. The principal sample obtained the KMO value of 0,738, and the lowest value of MSA (Measure of Sampling Adequacy) is 0,556. The highest is 0,859 indicating communalities value appropriate matrix components. Loading factors on all variables are above 0,40, and all factors on the leadership training instruments for the principal of Vocational High School have an AVE value greater than 0,5. The student sample obtained the KMO value is 0,682, the lowest value of MSA (Measure of Sampling Adequacy) is 0,556 and the highest is 0,859; communalities value and appropriate matrix components, loading factor on all variables are above 0,40, and all factors on the leadership training instruments for the principal of Vocational High School have an AVE value greater than 0,5. Thus, they have met reliability and can be accepted.